Financial sector and well-being: a participatory reflection. Project Financialization, Economy, Society and Sustainable Development – FESSUD WP5 – Task 5.6, Portugal, Prelimary Report. - Silva, Rita; Fernandes, L. C.; Pedro, Sérgio; Berham, Maria J.; Gonçalves, Raquel; Farinha, G. (2015)
This report refers to the research activities conducted by Habita – Association for housing and city rights, in the framework of work package 5 (WP5 - Financial sector and well-being) of the Project Financialization, Economy, Society and Sustainable Development – FESSUD, task 5.6. Firstly, in order to understand Portuguese specificities, we present an overview of the impact of financialization in social well being in Portugal. It's mentioned the peripherization path in the framework of the European Monetary Union (EMU), based on credit-oriented finacialization, with similarities to that observed in other countries of southern Europe. This path was strengthened in context of crisis and austerity, with significant economical and social impacts. In terms of economic impacts, we present the examples of agriculture and housing, in order to illustrate, respectively, the drastic reduction of the productive sectors and the deeper involvement of finance sector in the households quotidian. Both trends are particularly problematic in the context of crisis. In terms of social impacts, we highlight the way the austerity policies, relying in wage deflation and radical suspension of public investment, deepened and widened the economic vulnerabilities and precipitated an reconfiguration of the employment regime, increasing inequality and poverty. The research was designed to address two key research questions: How would finance look like if it happened on the terms of the socially disadvantaged? What reforms do socially disadvantaged regard as crucial to either achieve involvement on their terms or have an alternative financial system better serving their needs? The target of this participatory action-research is twofold: I) participants at risk of poverty and potentially excluded of the financial system; II) grass-roots alternative initiatives to mainstream financial system. A participatory reflection was designed in order to give voice to disadvantaged and marginalised groups; to capture a wide range of perspectives on the access to financial services and impact of these on well-being; and to explore possible paths of change. Accordingly, we identified several profiles of poverty risk and potential exclusion from financial system, which were the basis for organizing the five dialogue groups: unemployed; women at risk of poverty (WRP); residents in self-built neighborhoods (RSBN); Sex Workers (SW); small farmers (SF). Moreover, to identify the grass-roots alternatives to mainstream financial system, as well the constraints to their development, we complemented document al analysis of the manifesto of the recently created Forum of Ethical and Solidary Finances with a small inquiry elaborated for this purpose. One of the most relevant results lies in the fact that the financial system, per se, was not the main concern of the participants in the dialogue groups. The detachment toward the financial system does not seem, however, to mean indifference. Lack of transparency, distrust, precariousness, distress and burden of debts, inequality of negotiating power, and inadequacy of credits to the needs, are some of the key concepts emphasized in the relation to the financial system. Work, public policies, welfare state and market regulation are the changes most wanted. The credit system does not allow to have access to essential goods, for those who live in poverty. People in poverty or disadvantage need crucial changes in the structural conditions of society. The financial system and the structural conditions of society are deeply interwoven. Whereas the financialization is associated to a more unequal society it's necessary to definancialize the economy and the society. Alternative finance experiences are developed around the concepts of ethics and solidarity as opposed to mainstream finance, promoting financial instruments that guarantee transparency, participation and support for high social and environmental value projects for the community that have no response from conventional system. However, they have major limitations due to lack of institutional support and resources.